Recent Advances in Atmospheric, Solar-Terrestrial Physics and Space Weather From a North-South network of scientists [2006-2016] PART B : Results and Capacity Building - Amory Mazaudier, Christine (2017)
This paper reviews scientific advances achieved by a North-South network between 2006 and 2016. These scientific advances concern solar terrestrial physics, atmospheric physics and space weather. This part B is devoted tothe results and capacity building. Our network began in 1991, in solar terrestrial physics, by our participation in the two projects: InternationalEquatorial Electrojet Year IEEY [1992-1993] and International Heliophysical Year IHY [2007-2009]. These two projects were mainly focused on the equatorial ionosphere in Africa. In Atmospheric physics our research focused on gravity waves in the framework of the African Multidisciplinary Monsoon Analysis project n°1 [2005-2009 ], on hydrology in the Congo river basin and on lightning in Central Africa, the most lightning part of the world. In Vietnam the study of a broad climate data base highlighted global warming. In space weather, our results essentially concern the impact of solar events on global navigation satellite system GNSS and on the effects of solar events on the circulation of electric currents in the earth (GIC). This research began in the framework of the international space weather initiative project ISWI [2010-2012]. Finally, all these scientific projects have enabled young scientists from the South to publish original results and to obtain positions in their countries. These projects have also crossed disciplinary boundaries and defined a more diversified education which led to the training of specialists in a specific field with knowledge of related scientific fields.